Parenting practices and antisocial behavior in adolescentsin conflict with the law - Cabrera Gutiérrez, Germán; Londoño Arredondo, Nora Helena; Arbeláez Caro, Joan Sebastián; Álvarez Martínez, María Camila; Gamboa Hernández, Andrés Mauricio (Pensando Psicología, 2021)
Objective: Establish the relationship between parenting practices and antisocial behavior in adolescents linked to the criminal responsibility system for adolescents. Method: The present study was framed in a quantitative, descriptive-correlational research of transversal temporality. The population was adolescents linked to the criminal responsibility system and the sample was determined following a non-probabilistic-intentional sampling. In total, 70 adolescents linked to the criminal responsibility system participated. Instruments: Characterization sheet, scale of parental practices by Andrade and Betancourt (2008) and the neuropsychiatric interview for adolescents. Results:  80% of the population reported antisocial behavior disorder, it was also found that maternal behavioral control has a significant difference from the group of people with antisocial disorder (U = 1134,500; p = .014) and in case of the gender group, the difference was in maternal psychological control (U = 354,000; p = .00). The maternal behavioral control was related to the disorder of disocial behavior (Coef. = .222; p = .014 ≤ .05). Maternal psychological control and gender were related (Coef. = .240; p = .00 ≤ .01). Conclusions: The determining variable in the case of the sample of adolescents with antisocial behavior was maternal behavioral control and according to gender was the psychological control, confirming the importance of the influence of maternal practices in the construction of prosocial behavior in teenagers.
Keywords: dissocial behavior; adolescent behavior; prosocial behavior; parental responsibility